2018 Vegetable Production Handbook Chapter 16: Strawberry Production - Vance M. Whitaker; Nathan S. Boyd; Natalia A. Peres; Johan Desaeger; Joseph W. Noling; Justin Renkema (EDIS, 2018)
This 21-page fact sheet is chapter 16 of the 2018 Vegetable Production Handbook. Written by Vance M. Whitaker, Nathan S. Boyd, Natalia A. Peres, Johan Desaeger, Joseph W. Noling, and Justin Renkema, and published by the Horticultural Sciences Department, 2018.